Experiments as a Tool of Verifying Efficiency of Implicitly Agreed-Upon Market Organizations - Jakubowski, Rafał M.; Kuśmierczyk, Paweł (Ekonomika, 2008)
We analyse the possibility of an experimental study of the efficiency of market institutional structures. In the paper “On the new institutionalism of markets: the market as an organization” by R. Richter, the implicitly agreed upon market organization is regarded as a Nash equilibrium of a game between potential market participants. The solution of such coordination problem is not necessarily Pareto-efficient but could be efficient given assumptions of New Institutional Economics (i. e. could be NIE-efficient). This framework can be very helpful as a descriptive tool used to explain the persistence or transition of market institutions, but in can be difficult to be verified empirically. Economic experiments have been successfully applied to analyse market institutions and to compare their efficiency. In the paper, we demonstrate how this methodology could be used to analyse the “spontaneous” market organizations reached as a tacit agreement in a coordination problem. We also advocate that economic experiments can be a very useful tool to verify the efficiency of such institutions.